Educational-spiritual and ethnomental components of Eastern Christianity - Стадник, M.; Кудин, O. (Київський національний університет імені Тараса Шевченка, 2026)
B a c k g r o u n d . In the context of the treacherous Russian aggression that has led to the absurd Russian-Ukrainian war in the 21st century, new dimensions of Ukrainian national identity have emerged, prompting the search for new approaches to the educational process and scholarly understanding in general. Ukrainian identity has been shaped by various historical, religious, cultural, and ethnonational factors. Among them, the Orthodox and Greek Catholic traditions, along with elements of the ancient Slavic worldview, have played a decisive role, being reflected in customs, character traits, and value orientations. M e t h o d s . The historical method was applied to analyze sources and educational institutions in order to trace the evolution of the relationship between religion and education in Eastern Christianity. The religious studies approach made it possible to define the specific features of theological education in the Eastern Christian tradition, which focuses on the interpretation of the Holy Scripture and Sacraments, liturgical and artistic practices, as well as the practical application of Christian principles in everyday life. To demonstrate how cultural phenomena (such as language), artifacts (ancient Rus' manuscripts), and symbols(the anthropological code) influence the formation of educational patterns, a cultural analysis was used. This approach helped to identify the initial worldview orientations of Byzantine education in the Ukrainian lands and their resonance in the construction of the modern educational process. R e s u l t s . The study of the historical and contemporary context of the interrelation between religion and education in shaping ethnomentality has revealed that religious educational systems tend to form ethnonational values that are organically integrated into the local sociocultural environment. Religious knowledge within the educational process contributes to the development of a unique ethnomentality that unites the historical heritage of the nation with contemporary realities. In essence, the ethnomental dimensions of cognition in the educational process of Eastern Christianity foster the formation of a worldview in which knowledge is integrated with the spiritual principles of faith. The main purpose of religious cognition is the "approach" to God and the moral and cultural perfection of Ukrainian ethnolife and the social order. C o n c l u s i o n s . Eastern Christianity represents a unique spiritual and cultural phenomenon in which theological, educational, and ethnocultural factors are harmoniously combined. Its foundation lies in spirituality aimed at achieving harmony between faith, knowledge, and the moral self-improvement of the individual. The Ukrainian ethnomental dimensions of the educational process within Eastern Christianity are crucial for understanding how culture, language, religion, and traditions influence the affirmation of spirituality and the development of education among different peoples. Using Ukraine as an example, one can observe the continuity of spiritual heritage and the origins of ethnonational worldview, which serves as a foundation for the intellectual and moral values of Ukrainian society.

В с т у п . Наголошено, що в умовах віроломної російської агресії, що призвела до абсурдної російсько-української війни у ХХІ столітті, висвітлились нові виміри української національної ідентичності, що зумовлює пошук нових шляхів до освітнього процесу та наукового пізнання загалом. Підкреслено, що українська ідентичність формувалася під впливом різних історичних, релігійних, культурних та етнонаціональних чинників. Серед них визначальними стали православна, греко-католицька традиції й елементи давньослов'янського світогляду, які відобразилися у звичаях, характері й ціннісних орієнтирах. М е т о д и . Використано історичний аналіз джерел та освітніх інституцій, щоб показати еволюцію зв'язку між релігією та освітою в східному християнстві. Метод релігієзнавчого аналізу дозволив сформулювати особливості богословської освіти у східному християнстві, що зосереджувалася на осмисленні Святого Письма та Святих Таїнств, літургійних та мистецьких практиках, а також на практичному застосуванні християнських принципів у житті. Аби показати, як культурні явища (мова), артефакти (давньоруські книги), символи (антропологічний код) тощо впливають на формування освітнього патерну, застосовано культурологічний аналіз, який дозволив виявити початкові світоглядні настанови візантійської освіти на теренах України та її відлуння у будові сучасного освітнього процесу. Р е з у л ь т а т и . У результаті вивчення історичного та сучасного контексту взаємозв'язку релігії та освіти у формуванні етноментальності виявлено, що релігійні освітні системи прагнуть формувати етнонаціональні цінності, які органічно інтегруються у місцевий соціокультурний простір. Акцентовано, що релігійне пізнання в освітньому процесі сприяє формуванню унікальної етноментальності, яка поєднує історичну спадщину етносу та сучасні реалії. Розкрито, що етноментальні виміри пізнання в освітньому процесі східного християнства сприяють формуванню світогляду, в якому знання інтегруються із духовними принципами віри, де головним завданням релігійного пізнання є "наближення" до Бога та вдосконалення українського етнобуття та морального життя соціуму. В и с н о в к и . Обґрунтовано, що східне християнство є унікальним духовно-культурним феноменом, у якому поєднуються богословські, освітні та етнокультурні чинники. Його основою виступає духовність, спрямована на гармонію між вірою, знанням і моральним самовдосконаленням особистості. Доведено, що українські етноментальні виміри освітнього процесу східного християнства є важливими для розуміння того, як культура, мова, релігія та традиції впливають на утвердження духовності, розвиток освіти в різних народів. На прикладі нашої країни показано тяглість духовної спадщини та витоки етнонаціонального світогляду, який є основою для розвитку інтелектуальних і моральних цінностей українського суспільства.
Освітньо-духовні й етноментальні складники східного християнства
Keywords: folk Christianity; religious faith; education; spirituality; Ukrainian ethnomentality; religious education; Eastern Christianity; confessional dominance; national identity; religious identity; народне християнство; релігійна віра; освіта; духовність; українська етноментальність; релігійна освіта; східне християнство; конфесійна домінанта; національна ідентичність; релігійна ідентичність